Deepfake en Ecuador: una mirada desde la cobertura periodística (Miscelánea) - Altamirano Molina, Marco Vinicio (2026)
This study analyzes news coverage of the October 2023 case in Quito, Ecuador, where two underage students created fake sexual content using artificial intelligence (DeepFake) using photographs of female classmates. Seven news stories published between October 4 and 7, 2023, from local, national, and international media outlets were analyzed. The analysis used categories related to news framing (legal, technological, denunciation), sources used (official, expert, interested, and citizen), and content tone (objective, denunciatory, neutral). The results, based on a qualitative study, indicate that most media outlets maintained objectivity and used reliable sources, but provided little depth on issues of gender-based violence and victims’ rights. Legal gaps were identified in the regulation of AI-generated sexual content in Ecuador, while the ethical debate centers on privacy, consent, and legal liability. This analysis underscores the need for an ethical media approach that respects the dignity of victims, prevents re-victimization, and promotes regulatory updates in light of emerging technologies such as artificial intelligence.